Platelet-rich plasma in the treatment of osteoarthritis – a systematic review - Rosiewicz, Magdalena; Bieńkowska, Karolina; Pastuszek, Aleksandra; Minda, Aleksandra; Janda, Anita; Bartolik, Sylwia; Durowicz, Marcin; Górnicka, Iwona; Drzymała, Jan; Kierepka, Urszula (Quality in Sport, 2025)
Introduction: Platelet-rich plasma (PRP) is an autologous preparation gaining popularity in regenerative medicine. It is prepared from a patient’s blood by centrifugation, which results in a much higher concentration of platelets than in a standard sample. The rich content of growth factors and signaling molecules provides proliferative and regenerative effects on other cells. These properties are generating considerable interest in plasma for the treatment of degenerative diseases. Purpose: This systematic review analyzes the evidence from different studies evaluating the validity of platelet-rich plasma in the treatment of degenerative diseases. Materials and Methods: The article was written based on scientific papers available on PubMed and Google Scholar. Results: Platelet-rich plasma has demonstrated beneficial effects on joint health in patients with osteoarthritis (OA). Most studies report pain reduction and improved joint function following PRP treatment. When combined with other agents, such as hyaluronic acid, PRP may have synergistic effects. The most favorable outcomes are observed in younger patients with early-stage OA. Conclusions: PRP injections may represent a significant component of osteoarthritis (OA) treatment. However, this approach requires standardization in terms of preparation methods, concentration of individual components, as well as the volume and frequency of administration. Keywords: osteoarthritis, platelet-rich plasma, cartilage, intra-articular treatment, hyaluronic acid, LP-PRP, LR-PRP